2002
DOI: 10.1079/bjnbjn2002570
|View full text |Cite
|
Sign up to set email alerts
|

Dietary fat source regulates ob gene expression in white adipose tissue of rats under hyperphagic feeding

Abstract: This work was designed to investigate the effect of different lipid sources on ob gene expression and serum leptin levels in rats with two different feeding protocols: (1) free access to food; or (2) energy-controlled feeding. Male Wistar rats were fed diets containing 40 % energy as fat (olive oil, sunflower oil or beef tallow), for 4 weeks. In Expt 1 rats had free access to food, and in Expt 2 rats were fed a controlled amount of food (16 g/d, equivalent to 300 kJ/d). Insulin and leptin were determined by EL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…MUFAs are common in many foods but are enriched in a variety of foods including nuts, avocados, and olive oil. Evidence from model organism studies through clinical trials bear out the effects of MUFAs and/or olive oil on improvements in oxidative metabolism and energy expenditure (Børsheim et al, 2006;Rodrı ´guez et al, 2002;Shin and Ajuwon, 2018) and in disease prevention and lifespan extension (Buckland and Gonzalez, 2015;Estruch et al, 2006;Han et al, 2017;Salas-Salvado ´et al, 2011;Hoffmann, 2014a, 2014b;Schwingshackl et al, 2011;Trichopoulou et al, 2005). Importantly, MUFAs are regarded as one of the key components of the Mediterranean Diet, which is well established to have wide-ranging health benefits including reduced agingrelated diseases and overall mortality (Sofi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…MUFAs are common in many foods but are enriched in a variety of foods including nuts, avocados, and olive oil. Evidence from model organism studies through clinical trials bear out the effects of MUFAs and/or olive oil on improvements in oxidative metabolism and energy expenditure (Børsheim et al, 2006;Rodrı ´guez et al, 2002;Shin and Ajuwon, 2018) and in disease prevention and lifespan extension (Buckland and Gonzalez, 2015;Estruch et al, 2006;Han et al, 2017;Salas-Salvado ´et al, 2011;Hoffmann, 2014a, 2014b;Schwingshackl et al, 2011;Trichopoulou et al, 2005). Importantly, MUFAs are regarded as one of the key components of the Mediterranean Diet, which is well established to have wide-ranging health benefits including reduced agingrelated diseases and overall mortality (Sofi et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…This suggests a new form of leptin-mediated lipolysis. The possibility cannot be ruled out that the n-9 fatty acids induce a modification of leptin metabolism and that, either alone or interacting with lipolytic hormones, they can modify lipolytic activity (Rodríguez et al 2002a). Greater accumulations of adipose tissue can increase the levels of circulating leptin, which in turn would increase adipose tissue lipolytic activity (Martínez et al 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Fatty acids may influence the expression of adipokines like leptin and resistin directly by interaction with transcription factors, or indirectly via unknown mechanisms possibly linked to fatty acid oxidation, synthesis or storage 39 . It has been reported that dietary monounsaturated and polyunsaturated fatty acids may modify plasma leptin concentration in human, rat and mice, by means of a decrease in leptin gene expression both in vivo and in vitro , mediated by mechanisms associated with reduced PPARγ and SREBP-1 gene expression 40 , 41 . Moreover, it has been shown that resistin is inhibited by polyunsaturated fatty acids.…”
Section: Eicosanoid and Adipokine Productionmentioning
confidence: 99%